A New Time-of-Flight Extraction Method for Narrowband Lamb Wave in Metallic Plate - Zhe Wang; Songling Huang; Qing Wang; Shen Wang; Wei Zhao (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Lamb wave is potential to evaluate the health state of plate-like structures in nondestructive testing. However, the dispersive and multimodal properties of Lamb wave bring negative effect on the extraction of time-of-flight (TOF) which is important information to map the structure. This paper proposes a new method based on the ridge analysis to accurately extract the TOF of narrowband Lamb wave. The method establishes the ridge curve in the time-frequency domain and then, the TOF of corresponding frequency can be obtained utilizing the time information in the ridge. An experiment system using the electromagnetic acoustic transducer is established on the steel plate to verify the performance of the proposed method. The results show that the ridge analysis method has higher accuracy than the traditional Hilbert Transform method. Furtherly, the sensitive analysis proves that the proposed method owns high stability and strong robustness.